SOSIALISASI PENGELOLAAN KEUANGAN DIKALANGAN REMAJA DI DESA GANDOANG - Bayu Kurniawan; Mita Widyastuti; Dila Novita (Universitas Islam 45 Bekasi, 2022)
Teenagers are people who are very consumptive in using their pocket money. A teenager's financial expenditure is influenced by the teenager's own desire to spend it. One of the causes is the influence of peers and the lifestyle they live. Managing finances since adolescence is an important thing to do, but there are still many teenagers who have not been able to manage their finances properly. This can happen because of the psychological aspects of teenagers who are just growing up and influences from outside themselves. The purpose of this financial management socialization activity is to increase the knowledge and skills of youth in managing personal finances effectively. The methods used in community service activities are mediation, socialization and training on the use of applications. The result of this activity is an increase in adolescent knowledge regarding how to manage finances. There is also an increase in knowledge related to data in investing in adolescents.